Preventing work-related musculoskeletal disorders in VDT users: a comprehensive health promotion program. - Wilkens PM (Work, 2003)
As we enter the 21st century, technology has revolutionized the workplace, as nearly half of the working population in the United States currently uses a computer at work. Although computers continue to effectively improve productivity in the workplace, the adverse effects of prolonged computer use on the musculoskeletal system cannot go unnoticed. The astounding rise in computer use in the last decade has been paralleled by a rise in work-related musculoskeletal disorders due to repetitive typing or key entry. Because national ergonomic standards aimed at reducing these injuries have not yet been enforced, the prevention of this national health problem lies in the hands of health care professionals. The following will outline a comprehensive health promotion program, based on Green and Kreuter's PRECEDE-PROCEED model, to serve as an example of how health professionals across the nation can begin to effectively prevent this astronomical problem.